2003
DOI: 10.1088/0268-1242/18/6/316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the linewidth enhancement factor on filamentation in 1.55  m broad-area laser diodes

Abstract: Broad-area laser diodes with different linewidth enhancement factors (α-factors) of 2 and 4 have been fabricated on 1.55 µm multi-quantum well structures. Far-field measurements show that the filamentation of the laser diodes is closely related to the α-factor. The full width at half maximum (FWHM) of the far-fields and the filamentation were reduced in the laser diodes with smaller α-factors. As the injection current increased, the FWHM of the far-fields also increased regardless of the value of the α-factor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Besides that, they showed that spatial frequency selection in inhomogeneously broadened lasers becomes independent of the linewidth enhancement factor α and cavity detuning in opposition to the homogeneous broadened case. The role of this parameter in spatial dynamics was previously studied by several authors [35,36]. A larger value of this factor leads to an increase of filamentation.…”
Section: Discussion Of the Resultsmentioning
confidence: 89%
“…Besides that, they showed that spatial frequency selection in inhomogeneously broadened lasers becomes independent of the linewidth enhancement factor α and cavity detuning in opposition to the homogeneous broadened case. The role of this parameter in spatial dynamics was previously studied by several authors [35,36]. A larger value of this factor leads to an increase of filamentation.…”
Section: Discussion Of the Resultsmentioning
confidence: 89%
“…The nearfield-image and far-field-pattern of the tapered ridge LD with linear variation waveguide show more stable output beam in spite of kink in light-current characteristics. The sub-modes in BALD as shown in near-field image make wide divergence angle in the horizontal direction [10] but sub-mode does not change and thus there is no kink. But in the tapered ridge LD, there seems to be competition in single mode and other modes.…”
Section: Laser Diode Structure Desginmentioning
confidence: 95%